Postfoucaultowska analiza dyskursu o edukacji. Uwagi warsztatowe - Nowicka-Franczak, Magdalena (Kultura-Społeczeństwo-Edukacja, 2019)
Postfoucauldian discourse analysis is a vigorously developing approach to discourse studies focusing on the analysis of power, discourse, knowledge and social practice. This comprises studies deriving from Michel Foucault’s thought, reinterpreting it, however, with the aim at application to an analysis of empirical data, also from the field of pedagogy and education. The purpose of this paper is to present main concepts and categories of postfoucauldian discourse analysis (e.g. enunciation, discursive formation, discursive practice, procedures for the control of discourse, dispositive, regime of truth) and guidelines for conducting research on the example of an analysis of chosen public texts concerning the debate on liquidation of middle schools in Poland as a result of the reform of education carried out by Law and Justice’ government.